2009
DOI: 10.1016/j.jmaa.2009.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Existence and multiplicity of positive solutions for classes of singular elliptic PDEs

Abstract: We consider the boundary value problemwhere Ω ⊂ R N is a bounded domain, φ is a nonnegative function in L ∞ (Ω) such that φ > 0 on some subset of Ω of positive measure, and g : [0, ∞) → R is continuous. We establish the existence of three positive solutions when g(0) > 0 (positone), the graph of s α+1 g(s) is roughly S-shaped, and α > 0. We also prove that there exists at least one positive solution when g(0) < 0 (semipositone), g(s) is eventually positive for s > 0, and 0 < α < 1.We employ the method of sub-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…However, our multiplicity result is restricted two positive solutions. In [1], the author studied this singular problem (2) when p = 2 by treating it as a limit problem of the class of non-singular problems defined by −∆u ǫ = λ e αu α+u (u+ǫ) β in Ω and u ǫ = 0 on ∂Ω. Here we establish the our results for all p > 1 directly by method of sub-and supersolutions associated with such singular problems.…”
Section: Introductionsupporting
confidence: 54%
“…However, our multiplicity result is restricted two positive solutions. In [1], the author studied this singular problem (2) when p = 2 by treating it as a limit problem of the class of non-singular problems defined by −∆u ǫ = λ e αu α+u (u+ǫ) β in Ω and u ǫ = 0 on ∂Ω. Here we establish the our results for all p > 1 directly by method of sub-and supersolutions associated with such singular problems.…”
Section: Introductionsupporting
confidence: 54%
“…(c) In case of M + λ,Λ (D 2 u) = ∆u, the existence of positive classical solution to (1) has been established in [22,28,30,48]. In this continuation, we also mention the work [14], where authors establish the existence of positive solution to (1) with M + λ,Λ (D 2 u) = ∆u, H ≡ 0 and f (0) < 0. So our works generalize these works to fully nonlinear elliptic equations in the framework of viscosity solution.…”
Section: Jagmohan Tyagi and Ram Baran Vermamentioning
confidence: 93%
“…For the sake of completeness, we also discuss the existence of a positive solution to (1) in case f (0) < 0. The existence result for the case f (0) < 0 is motivated by the study of similar problems but in the context of Laplace equation, see [14]. The article is organized as follows.…”
Section: Jagmohan Tyagi and Ram Baran Vermamentioning
confidence: 99%
“…It has been observed that very few papers exist in the literature on the existence of at least two positive solutions of (1.1) and (1.2). Maya and Robinson [22] used supersolution and subsolution method to obtain sufficient conditions for the existence of at least three positive solutions of the equation…”
Section: Introductionmentioning
confidence: 99%